2012
DOI: 10.1007/s12015-012-9368-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Derived Stem Cells Protect Skin Flaps Against Ischemia-Reperfusion Injury

Abstract: Overall, our study demonstrates that ADSCs treatment significantly enhances skin flap survival in the aftermath of ischemia to an extent that almost equals surgical results without ischemia. This effect is accompanied with a pronounced and significant angiogenic response and an improved blood perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 31 publications
4
39
2
Order By: Relevance
“…It was found that stem cell treatment significantly enhances skin flap survival in the aftermath of ischemia, to an extent that almost equals surgical results without ischemia. This effect is accompanied by a pronounced and significant angiogenic response and improved blood perfusion [28]. If these results can be confirmed by other studies, they will mark substantial progress in microsurgical reconstruction surgery.…”
Section: The Use Of Selected Sc Fractions In Plastic and Reconstructisupporting
confidence: 54%
“…It was found that stem cell treatment significantly enhances skin flap survival in the aftermath of ischemia, to an extent that almost equals surgical results without ischemia. This effect is accompanied by a pronounced and significant angiogenic response and improved blood perfusion [28]. If these results can be confirmed by other studies, they will mark substantial progress in microsurgical reconstruction surgery.…”
Section: The Use Of Selected Sc Fractions In Plastic and Reconstructisupporting
confidence: 54%
“…Cells at P4, which still possessed multipotent differentiation potential (Figure 2), were used for transplantation in this study. Compared with similar studies, the number of cells injected in this study was higher than others [8,[30][31][32][33]. Despite this, cells expanded at passage 6 could increase the number of cells for injection, but did not improve the protective effects in skin flap survival (data not shown).…”
Section: Discussioncontrasting
confidence: 79%
“…Although the mean survival area ratios in the ADSCs treatment group and in the BMSCs treatment group had no significant difference, higher levels of bFGF and VEGF were found in the BMSCs transplantation group [21] . In addition, ADSCs also had a significantly angiogenic response [22] , better immune compatibility and potential for enhancing the blood supply. These together suggest that both ADSCs and BMSCs have proangiogenic effect, but their promoting angiogenesis mechanisms may be quite different.…”
Section: Mscs Therapy Against Pedicle Flaps Necrosismentioning
confidence: 99%